BIOMOLECULE QUANTIFICATION OF NUTRIENT SELECTED STRAINS - MRS. BHATIA AMRITA; MRS. ULFAT BAIG; SHAIKH NAAZNEEN; CYRIL PRISCILLA (International Journal of Pharma and Bio Sciences, 2013)
Aging is a complex process and it is obvious in macroscopic organisms. In organisms like yeast, Drosophila, E coli etc there is a greater potential to identify the molecular mechanisms involved but identifying and quantifying aging is harder. Molecular damage includes DNA damage, protein damage and free radical attack for which the main targets are the macromolecules. Dietary restriction has shown to lower the rate of production of free radical reaction. Recent work in our laboratory has quantified biomolecules using nutrient selected strains of E.coli as it is a simple experimental model for studying aging. E.coli was subjected to extreme high and low nutrient conditions in order to determine their adaptability. The biochemical characteristics of the biomolecules and the differences in their cell content under two nutritional conditions were determined.